The Effect Chitosan Supplementation in The Diet on Fat and Cholesterol Levels of Duck Blood - Surahmanto, Surahmanto; Pagala, M. A.; Sandiah, N.; Fitrianingsih, Fitrianingsih (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The Effect Chitosan Supplementation in The Diet on Fat and CholesterolLevels of Duck Blood